2004
DOI: 10.1016/j.fertnstert.2004.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructure of collagen fibrils in uterine leiomyomas and normal myometrium

Abstract: Objective-To examine the ultrastructural characteristics of extracellular matrix and mature collagen fibrils in uterine leiomyomas and compare them with those in adjacent normal myometrium.Design-Analysis of paired leiomyoma-myometrium in surgical specimens. Setting-Research center and tertiary care center.Subject(s)-Women undergoing medically indicated hysterectomy for symptomatic uterine leiomyomas. Intervention(s)-None.Main Outcome Measure(s)-Appearance and spatial orientation of the collagen fibrils in lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 28 publications
(38 reference statements)
3
133
0
3
Order By: Relevance
“…Fibrotic leiomyomas (Fig. 1B) consist of abundant collagen fibrils arrayed in a nonparallel manner, whereas in healthy myometrium there are sparse and well-aligned collagen bundles adjacent to smooth muscle cells Leppert et al, 2004). This irregularly arranged collagen could be a reason for the identified lower degree of anisotropy (i.e., less structure) in the leiomyomas compared to adjacent myometrium (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Fibrotic leiomyomas (Fig. 1B) consist of abundant collagen fibrils arrayed in a nonparallel manner, whereas in healthy myometrium there are sparse and well-aligned collagen bundles adjacent to smooth muscle cells Leppert et al, 2004). This irregularly arranged collagen could be a reason for the identified lower degree of anisotropy (i.e., less structure) in the leiomyomas compared to adjacent myometrium (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…ECM proteins formed by leiomyoma cells include collagens, proteoglycans and fibronectin. In addition to alterations in composition, the ultrastructure of collagen fibrils in leiomyoma is altered in both structure and orientation compared with normal myometrium (150). In fact, this disordered matrix represents the major part of the tumor (151) and is responsible for most of the symptoms (152).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…In addition to the smooth muscle component, they also possess a significant extracellular matrix consisting of fibroblasts [26]. They are therefore highly fibrous with the collagen fibrils randomly oriented, a characteristic different from the adjacent myometrium in which the collagen fibrils are aligned in an orderly fashion [20,30]. Clinically relevant myomas can be several centimetres in diameter and are usually fully vascularised, with angiogenesis continuously taking place; the absence of necrotic regions in most myomas [11] distinguishes them from other large solid tumours, where poorly vascularised necrotic zones are a prominent feature in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of myomas, the presence of oestrogen and progesterone up-regulates expression of a plethora of growth factors both within myocytes and fibroblasts, enhancing cell proliferation and collagen deposit [26], while at the same time the change in homeostasis in myomas accompanied by altered mechanical stresses, suggests the interplay between the chemical and mechanical effects and the role of stress in cell growth and fibroid development [20]. In vitro studies on tumour spheroids have also demonstrated resistance to tumour growth as a result of stress accumulated both within the tumour as well as in the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%